2020
DOI: 10.1021/acsomega.0c01034
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-l-cysteine Enhances the Effect of Selenium Nanoparticles on Cancer Cytotoxicity by Increasing the Production of Selenium-Induced Reactive Oxygen Species

Abstract: Peritoneal carcinomatosis (PC) has an extremely poor prognosis, which leads to a significantly decreased overall survival in patients with peritoneal implantation of cancer cells. Administration of sodium selenite by intraperitoneal injection is highly effective in inhibiting PC. Our previous study found that selenium nanoparticles (SeNPs) have higher redox activity and safety than sodium selenite. In the present study, we examined the therapeutic effect of SeNPs on PC and elucidated the potential mechanism. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…While SeNPs administration at the dosages of 5 or 6 mg kg −1 led to 25 or 50% survival in healthy animals, coadministration with NAC (250 mg kg −1 ) enhanced the survival to 87.5 or 100%, indicating that NAC reduced SeNPs lethality as well. [ 236 ] Bidkar et al showed that SeNPs stabilized with pluronic F‐127 and loaded with paclitaxel (PTX) inhibit the growth of A549, HeLa, HT29 and MCF7 cells with IC 50 values of 13.8 × 10 −6 , 8.7 × 10 −6 , 4.8 × 10 −6 , and 5.4 × 10 −6 m , respectively, which represents an improved antitumor activity when compared with unloaded SeNPs. SeNPs@PTX induced apoptosis by two main mechanisms.…”
Section: Senps For Pharmaceutical Applicationsmentioning
confidence: 99%
“…While SeNPs administration at the dosages of 5 or 6 mg kg −1 led to 25 or 50% survival in healthy animals, coadministration with NAC (250 mg kg −1 ) enhanced the survival to 87.5 or 100%, indicating that NAC reduced SeNPs lethality as well. [ 236 ] Bidkar et al showed that SeNPs stabilized with pluronic F‐127 and loaded with paclitaxel (PTX) inhibit the growth of A549, HeLa, HT29 and MCF7 cells with IC 50 values of 13.8 × 10 −6 , 8.7 × 10 −6 , 4.8 × 10 −6 , and 5.4 × 10 −6 m , respectively, which represents an improved antitumor activity when compared with unloaded SeNPs. SeNPs@PTX induced apoptosis by two main mechanisms.…”
Section: Senps For Pharmaceutical Applicationsmentioning
confidence: 99%
“…This process leads to a rapid and selective hyper-accumulation of SeNPs in cancer cells, which causes catastrophic oxidative stress and cell death. This underlying concept relies on two observations: firstly, the presence of higher basal levels of ROS in cancer cells compared to normal cells; secondly, cancer cells possess lower tolerance to increased levels of ROS than normal cells [ 288 , 292 , 293 ]. The process of ROS production, mediated by SeNPs, is illustrated in Figure 5 .…”
Section: Properties Of Selenium Nanoparticlesmentioning
confidence: 99%
“…The intraperitoneal delivery of SeNPs has emerged as an effective and safe approach in preventing the growth of cancer cells in the peritoneal cavity without remarkable liver toxicity symptoms [ 294 ]. For example, Zhao et al demonstrated that SeNPs delivered to hepatocarcinoma-22 cells in the peritoneal cavity of mice induce ROS production and cause protein degradation and apoptotic response [ 293 ]. This study showed that GSH can stimulate a dose-dependent redox biotransformation of SeNPs to generate ROS in a pure enzymatic system, especially given that GSH is the cell’s most abundant thiol-containing small molecule.…”
Section: Properties Of Selenium Nanoparticlesmentioning
confidence: 99%
“…The way selenium acts on cancer cells involves the production of ROS and modification of the thiol group. This procedure brings about effects that disrupt transcription and changes related to the endoplasmic reticulum (Zhao et al, 2020[ 86 ]; Razaghi et al, 2021[ 59 ]). It is worth noting that selenium may be helpful in the treatment of advanced forms of cancer through its cytotoxic effect that damages cancer cells.…”
Section: The Role Of Selenium In Different Diseasesmentioning
confidence: 99%